The effectiveness of foreign military assets in natural disaster response - Wiharta, Sharon (Stockholm : Stockholm International Peace Research Institute, 2008)
This study provides an overview of the current use of foreign military assets in natural disaster response, including how and why they are deployed. It also analyses the role played by foreign military assets in several major disaster relief operations: in Mozambique following the floods in 2000, in Haiti following floods and tropical storm Jeanne in 2004, in Aceh province, Indonesia, following the Indian Ocean tsunami of 2004, and in Pakistan-administered Kashmir following the South Asia earthquake of 2005.
Includes bibliographical references.
Mode of access; World Wide Web.
Keywords: Disaster relief; Armed Forces -- Civic action; Emergency management